Factors predicting pharyngocutaneous fistula in patients after salvage laryngectomy for laryngeal malignancy – A multicenter collaborative cohort study. (November 2022) - Fitzgerald, Conall W.R.; Davies, Joel C.; de Almeida, John R.; Rich, Jason T.; Orsini, Mario; Eskander, Antoine; Monteiro, Eric; Mimica, Ximena; Mclean, Tim; Cracchiolo, Jennifer R.; Ganly, Ian; Hessel, Amy; et al.
Highlights: Pharyngocutaneous fistula is a major complication of salvage laryngectomy. We present a large, international experience with percutaneous fistula following salvage laryngectomy. Positive surgical margin is the single most significant factor in predicting post-operative fistula. The role of vascularized free flap reconstruction in preventing post-operative fistula remains to be fully understood. Abstract: Objectives: Pharyngocutaneous fistula (PCF) is a major morbidity of salvage total laryngectomy (TL). Understanding the factors predicting PCF is fundamental to managing laryngeal cancer. We aim to assess factors associated with PCF following salvage TL in a multicenter, international retrospective cohort study of academic centers in the US and Canada. Results: In total, 550 patients post-salvage TL were identified (mean [SD; range] age, 64 [10.4; 32–90] years; 465 [85 %] male and 84 [15 %] female) between 2000 and 2014. Rate of PCF was 23 % (n = 127) with median time to PCF of 2.9 weeks. Surgical management of PCF was required in 43 % (n = 54) while 57 % (n = 73) required wound care alone. Rates of PCF differed by primary treatment modality [radiation, 20 % (n = 76); chemoradiation, 27 % (n = 40); not available (n = 6)] and use of vascularized tissue in pharyngeal closure [free/regional flap, 18 % (n = 25); no vascularized tissue/primary closure, 24 % (n = 98); not available (n = 4)]. There was no statistically significant association between PCF and treatment with chemoradiation (HR, 1.32; 95 % CI, 0.91–1.93, p = 0.14) or lack of vascularized tissue reconstruction (HR, 1.41, 95 % CI 0.91–2.18, p = 0.12). Significant association between PCF and advanced stage (T3 or T4), positive margin, close margin (<5mm), lymphovascular invasion and pre-operative tracheostomy were identified on univariable analysis. Positive surgical margin (HR, 1.91; 95 % CI, 1.11 to 3.29) was the only significant association on multivariable analysis. Conclusion: We highlight positive surgical margin as the only variable significantly associated with increased risk of PCF following salvage TL on multivariable analysis in a large cohort across several major head and neck oncology centers.